Effects of dietary xylooligosaccharides on growth performance, immunity and Vibrio alginolyticus resistance of juvenile Litopenaeus vannamei. (18th November 2018) - Sun, Yuping; Wang, Guoxia; Peng, Kai; Huang, Yanhua; Cao, Junming; Huang, Wenqing; Chen, Bing; Hu, Junru
Abstract: A 60‐day feeding trial was conducted to assess the effects of xylooligosaccharides on growth performance, immunity and Vibriosis alginolyticus resistance of juvenile Litopenaeus vannamei . Five diets were formulated to contain 0 (T0), 1 (T1), 2 (T2), 4 (T4) and 6 (T6) g/kg of xylooligosaccharides, triplicate groups of 40 shrimps with initial weight of 0.10 ± 0.01 g were fed to apparent satiation four times daily. At the end of the feeding trail, ten shrimps from each tank were challenged with V. alginolyticus . Results showed that shrimps fed xylooligosaccharides containing diets had higher ( p  < 0.05) feed efficiency, survival rate and intestinal villi length and area than those of T0. There was no significant difference in final body weight, weight gain rate and chemical compositions of whole shrimp among treatments. Shrimps fed T4 and T6 diets had higher ( p  < 0.05) phenoloxidase and lysozyme activities than those in T0. Concentration of albumin, phenoloxidase activity and survival rate of shrimps decreased ( p  < 0.05) after 72 hr of challenge, with SR being greater ( p  < 0.05) in T2, T4 and T6 than that of in T0. Results demonstrate that supplementing 4–6 g/kg of xylooligosaccharides in diets increased feed efficiency, survival rate, intestinal villi length and area, and improved the resistance of juvenile L. vanname i against V. alginolyticus . This study suggests that xylooligosaccharides could be a potential feed additive in practical diet of juvenile L. vannamei .